An essential technique for modern hepato-pancreato-biliary surgery: minimally invasive biliary reconstruction. (4th March 2021) - Wu, Jiacheng; Xiang, Yien; You, Guangqiang; Liu, Zefeng; Lin, Ruixin; Yao, Xiaoxiao; Yang, Yongsheng
ABSTRACT: Introduction : Minimally invasive reconstruction of the biliary tract is complex and involves multiple steps. The procedure is challenging and has been an essential technique in modern hepato-pancreato-biliary surgery in recent years. Additionally, the quality of the reconstruction directly affects long-and short-term complications and affects the prognosis and quality of life. Various minimally invasive reconstruction methods have been developed to improve the reconstruction effect; however, the optimal method remains controversial. Areas covered : In this study, were viewed published studies of minimally invasive biliary reconstruction within the last 5 years and discussed the current status and main complications of minimally invasive biliary reconstruction. More importantly, we introduced the current reconstruction strategies and technical details of minimally invasive biliary reconstruction, which may be potentially helpful for surgeons to choose reconstruction methods and improve reconstruction quality. Expert opinion : Although several improved and modified methods for biliary reconstruction have been developed recently, no single approach is optimal or adaptable to all situations. Patient-specific selection of appropriate technical strategies according to different situations combined with sophisticated and skilled minimally invasive techniques effectively improves the quality of anastomosis and reduces complications.